(untitled) (Journal of the College of Basic Education, 2022)
The current research sought to study the directorial methods of the posters of the international competition held in Baghdad in 1982, which included the participation of designers from Iraq, the Arab countries and the world, to expose the criminal act carried out by Israel in striking the peaceful Iraqi nuclear reactor through the creative ideas and directorial methods of the aforementioned posters, which shook the peaceful peoples. Around the world.